Penentuan Lokasi Potensial dan Arahan Pengembangan Kawasan Perdagangan Secara Berkelanjutan Di Kota Masamba - Widiya N, Munika; Sastrawati, Isfa; Akil, Arifuddin (Prodi PWK Universitas Tadulako, 2025)
The development of trade and services in the Masamba Urban Area forms a linear pattern on the main roads. In addition, in transitional areas and peripheral areas the existing trade and services are less developed, so the service orientation must be to the central area and the burden on the central area becomes heavy. The high intensity of activities along the main roads of the area creates a attraction and generation that can be one of the factors causing transportation problems (traffic congestion). The aim of this research are 1) to identify the factors that affects the development of trade area in Masamba Urban Areas, 2) to determine the potential locations of trade area in Masamba Urban Areas, 3) to formulate the direction of sustainable trade area development in Masamba Urban Areas. The data used consist of secondary data including demographic data, trade facilities, road networks, public facilities and infrastructure. Data collection was carried out by field surveys, mapping, questionnaires, and interviews. The analysis technique used are multiple linear regression analysis dan spatial analysis in the form of grid-based analysis. The results of the research on regression analysis show that the variables that have a significant effect on the development of trade areas in the Masamba Urban Areas include Demographics (X1), Public Facilities (X3), and Government Policy (X4), while Accessibility (X2) has no significant effect. Furthermore, based on the results of the grid-based analysis, three value categories are obtained, namely Very Potential (Values 23-30), Potential (Values 15-22), and Not Potential (Values 7-14), where most of the Masamba Urban Areas is included in the potential category.